Employee work passion in the South African workplace. - Fhatuwani Papinianus, Lidovho (My University, 2017)
The research conducted advances a description of the concept of passion according to the dualistic model and explores the uniqueness of this concept in the workplace. Additionally the research clarifies the interplay between passion and engagement and attempts to assess the impact these two concepts have on workplace performance in a South African context. The research shows that there is a positive correlation between passion and engagement and that engagement seems to have a stronger impact on performance, in all its forms, when compared to passion. Additionally harmonious passion is the only mode of passion that has an impact on workplace performance. The applied, and conceptual, implications of passion and engagement in business are discussed and recommendations are given.
MBA Thesis
Keywords: Employee motivation -- South Africa,Personnel management ,Achievement motivation -- Performance -- South Africa